التكيف المدرسي وعلاقته بالتحصيل الدراسي لدى المتأخرين في مادة الرياضيات دراسة ميدانية لدى عينة من تلاميذ سنة أولي ثانوًية بمدينة الأغواط - صريفيح فاطمة; مراد كلثوم; النوعي بدرية (My University, 2019)
To reveal the relationship between school adjustment and academic achievement. -Identify the differences in terms of the school adaptation variable among the delayed pupils according to gender variable and specialization. -Identification of the differences in relation to the variable scholastic achievement of the delayed pupils according to gender variable and specialization. Methodology: The methodology used is descriptive. Sample of the study: A sample of a group of students in the first year secondary school in Laghouat (60), 22 students and 38 students. The field of the study was based on the school adaptive measure to measure and compare the level of school adjustment for secondary school students who are late in math. This is a measure that has been modified by us as researchers to apply it to the research sample. The measure contains (59) (20), social (19),ملخص ‌ح academic adjustment (20) paragraph and two alternatives. The validity of the content was confirmed by the presentation of the tool to the arbitrators. The apparent honesty and honesty was calculated by using the Alpha Kronbach stability factor. And then unload them Program with the following statistical processors: arithmetic averages, standard deviations, percentages, Pearson correlation coefficient, Achtbarllfruq. Main results of the study: -There is a significant statistical correlation between school adjustment and scholastic achievement among students who are late in mathematics. -The level of school adjustment for students who were late in mathematics was average. -The level of achievement of students who were late in mathematics was above average. -There were no statistically significant differences in the level of school adjustment among latecomers in mathematics due to gender. -There were no statistically significant differences in the level of academic attainment among the late mathematicians due to gender. -There were no statistically significant differences in the level of school adjustment among latecomers in mathematics due to specialization. -There are no statistically significant differences in the level of academic achievement among the late mathematicians due to specialization.